Liberation Theology: A Critique of Modernity. Issue 5 (4th July 2017) - Andrade, Luis Martinez
Abstract : From 1492 onwards, the history and the appearance of the Americas acquired a new nature. The invasion of the Conquistadores is a critical moment not only in the constitution of modern western subjectivity, but also in shaping the pattern of world domination: in the words of Aníbal Quijano, "modernity, capitalism and Latin America were born the same day". Indeed, to understand the paradoxes and challenges of the Latin American people, one has to understand the self-destructive logic of capitalism's modernity–coloniality. Inspired by Walter Benjamin's project, this essay proposes a contrary reading of history in order to track the major colonial paradigms and the liberation struggles of its victims. Through evangelization, religion played an important role in the colonization of the indigenous imagination: myths, beliefs and legends of the Christian world were imposed on dominated societies. However, religion as the "sigh of the oppressed creature" (Marx) enabled the emergence of liberation Christianity: an ethos against colonial domination and against the idols of death. The theoretical expression of this liberating ethos was a school of thought that emerged in the mid-twentieth century in Latin America. Today, it is known as liberation theology. The theoretical and historical importance of liberation theology lies in its critique of the ideology of development, in its denunciation of the dynamics of modernity and in its fight against the idolizing of the market. Supported by Marxist and critical analysis, and applying categories borrowed from the social sciences, liberation theologians of both sexes made a radical reading of the Gospel and thus showed the fetish character of capitalism and the destructive dynamics of modernity. However, such criticism was always articulated to organizations and popular movements fighting for the radical transformation of society.